Serologic assessments in acute transfusion reactions: practices and yields. Issue 7 (7th August 2019) - Cohen, Robert; Lima, Ana; Escorcia, Alioska; Tasmin, Farzana; Lin, Yulia; Lieberman, Lani; Pendergrast, Jacob; Callum, Jeannie; Cserti‐Gazdewich, Christine
Abstract : Background & Objectives: Serologic testing after transfusion reactions (TRs) aims to find accountable immune haemolytic incompatibility. Our hospital policies recommend serologic testing in all TR, except for low‐risk fevers (subclinical temperature <39°C) or uncomplicated allergic reactions. Assessing compliance with these guidelines and serologic testing yields may provide insights on quality of practice and value. Materials & Methods: Interrogation of two haemovigilance databases identified all possible‐to‐definite TR over a 4‐year period (2013–2016) at four academic hospitals. We reviewed the performance and outcome of serologic testing by site, year, reaction type, implicated product and service. Results: Serologic testing occurred in 769 (55%) of 1408 referrals, with 1153 (82%) compliant with guidelines. Similar proportions deviated to overtesting (85/550 [15%]) and undertesting (174/858 [20%]), with undertesting seen most often in atypical TR. Overall, 30 (4.4%) of 769 cases had a new finding, but only 2 (0.3%) reflected host‐derived antibodies. Overall, the number needed to test to discover an unexpected allospecificity was 385, or 253 if limited to high‐risk fevers. Reaction‐ and product‐specific yields ranged from 0% to 48%. The yield in complicated allergic reactions was low at 2%, constituting only predictable passive isohaemagglutinin(s) in retrospect. Investigated IVIG TR accounted for most of this cohort's signal by passive isohaemagglutinins in 48%. Conclusion: The performance of post‐TR serologic testing revealed practice gaps and expected context‐specific yields. Tailored serologic testing (i.e. indirect antiglobulin tests for alloantibodies in post‐RBC/high‐risk febrile reactions, ± isoagglutinin‐focused tests after IVIG or ABO‐minor‐mismatched platelets) may improve value and liberate resources for other unmet needs in TR investigation.